Performance improvement of MO surge arrester using high gradient arrester block against VFTOs - Kannadasan Raju (IAES Indonesia Section, 2019)
It is well known that the metal oxide surge arrester is inoperative against very fast transients overvoltages (VFTOs) because of its strong stray capacitive effect. This stray effect causes a time lag between the peak of residual voltage and peak of the current surge and so there is a delay its response. In order to reduce the stray effect, high gradient material is used for preparing metal oxide arrester blocks with different compositions. For simulation study, the required electrical parameters of high gradient arrester blocks are calculated with estimated height of arrester. This model is simulated using Electromagnetic transient program (EMTP) for different arrester ratings against switching, lightning, steep and very fast transients. The simulated value of residual voltages are compared with experimental values. From the observed results, it is perceived that the newly developed high gradient arrester decreases the delay and so the dynamic performance of the arrester is improved especially against very fast transients.